2016
DOI: 10.1063/1.4960380
|View full text |Cite
|
Sign up to set email alerts
|

Cancelation of thermally induced frequency shifts in bimaterial cantilevers by nonlinear optomechanical interactions

Abstract: Bimaterial cantilevers have recently been used in, for example, the calorimetric analysis with picowatt resolution in microscopic space based on state-of-the-art atomic force microscopes. However, thermally induced effects usually change physical properties of the cantilevers, such as the resonance frequency, which reduce the accuracy of the measurements. Here, we propose an approach to circumvent this problem that uses an optical microcavity formed between a metallic layer coated on the back of the cantilever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…This rigidity arises from a nonlinear change in the CIRF caused by cantilever deflection and can be used to cancel the thermally induced frequency shift caused by bending. 14) Using a specific property of the OMC, i.e., the stored power follows a Lorentzian dependence on the position of the movable mirror making the cantilever and is enhanced orders of magnitude, we show that the cantilever has a higher absorption than that under direct irradiation. This absorption is maximum when the mirror is at the resonance position z P [see Eq.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…This rigidity arises from a nonlinear change in the CIRF caused by cantilever deflection and can be used to cancel the thermally induced frequency shift caused by bending. 14) Using a specific property of the OMC, i.e., the stored power follows a Lorentzian dependence on the position of the movable mirror making the cantilever and is enhanced orders of magnitude, we show that the cantilever has a higher absorption than that under direct irradiation. This absorption is maximum when the mirror is at the resonance position z P [see Eq.…”
mentioning
confidence: 87%
“…For this system, it is clearly shown that |E| 2 is enhanced many orders of magnitude. This implies enhancement of the absorbed power P(z) on the film, 14) which is given by…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, the singly and doubly clamped cantilevers are widely adopted in experiments and also in industry due to the simplicity in fabrication and high adaptability in using. The cantilever-based sensors were in the heart of experiments in fundamental physics [1][2][3][4] and in detecting of bio-objects [5][6][7][8], chemical substances [9,10], and physical properties [11,12]. In mass spectroscopy, to detect a mass ∆m that is adsorbed on the microcantilever surface, one usually examines the resonance frequency shift, which is related to ∆m via the formula [13],…”
Section: Introductionmentioning
confidence: 99%
“…T he application of bimaterial cantilevers in the metrology of atomic force microscopy has been of interest in several fields of biochemistry [1][2][3] and physics. [4][5][6][7][8][9][10] These measurements rely on the response of cantilevers under various effects due to the environment in which the sample or molecules are immersed. 4,11) Samples, such as virus molecules or bacteria, can be attached to or adsorbed on the cantilever surface and change the cantilever dynamics, as shown in Fig.…”
mentioning
confidence: 99%